2022
DOI: 10.1016/j.ajoc.2021.101236
|View full text |Cite
|
Sign up to set email alerts
|

Bilateral ptosis/blepharitis due to lepromatous leprosy

Abstract: Purpose To underscore the importance of histopathological evaluation in cases presenting with a constellation of unusual ocular inflammation and physical findings. Observation A 51-year-old male, presented with a chief complaint of worsening visual field loss due to droopy eyelids two months post excision of a right upper eyelid squamous cell carcinoma. His past medical history included chronic edematous facial features, chronic sinusitis, unexplained peripheral neuropa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 12 publications
0
2
0
Order By: Relevance
“…To our knowledge, only a few other leprosy cases have been reported as presenting in this fashion. Iqbal et al 21 reported a case of a 51-year-old man presenting with chronic bilateral ocular adnexal inflammation, eyelid swelling, ptosis, and blepharitis for 1–2 years in the United States. He was found to have lepromatous leprosy after histopathological evaluation showed noncaseating granulomatous perineural inflammation and acid-fast bacilli in the eyelid specimens.…”
Section: Discussionmentioning
confidence: 99%
“…To our knowledge, only a few other leprosy cases have been reported as presenting in this fashion. Iqbal et al 21 reported a case of a 51-year-old man presenting with chronic bilateral ocular adnexal inflammation, eyelid swelling, ptosis, and blepharitis for 1–2 years in the United States. He was found to have lepromatous leprosy after histopathological evaluation showed noncaseating granulomatous perineural inflammation and acid-fast bacilli in the eyelid specimens.…”
Section: Discussionmentioning
confidence: 99%
“…Neuronal injury in leprosy may present as weakness or may result in silent neuropathy, contracture, or atrophy [ 7 , 8 ]. Stocking and glove pattern of sensory damage is seen toward the lepromatous pole [ 9 , 10 ].…”
Section: Introductionmentioning
confidence: 99%